Multimedia Messaging for Social Change: Assessing the Impact of Multimedia Integration in Development Communication Campaigns - Udoudom, Uduak; Okon, Ememobong; Pam, Christiana; Brown, George (Journal of Community Service and Society Empowerment, 2024)
This research explores the transformative potential of multimedia messaging in development communication campaigns, with a focus on its impact on social change. As technology continues to advance, multimedia integration, encompassing elements such as text, images, audio, and video, has become a powerful tool for conveying messages and influencing behaviour. This study aims to assess the effectiveness and implications of incorporating multimedia into development communication initiatives. The paper examines various multimedia formats utilized in social change campaigns and assesses their influence on target audiences. By reviewing existing literature and case studies the study aims to identify patterns, challenges, and success factors associated with multimedia messaging. Additionally, attention is given to the role of digital platforms and social media in amplifying the reach and engagement of multimedia campaigns. Key considerations include the cognitive and emotional impact of multimedia messages, audience receptivity, and the potential for behaviour change. The research also investigates ethical considerations related to multimedia communication in the context of social change, addressing issues such as cultural sensitivity, inclusivity, and the potential for unintended consequences. Findings from this research will contribute valuable insights to the field of development communication, guiding practitioners, and researchers in optimizing the design and implementation of multimedia messaging strategies for effective social change. The overarching goal is to enhance our understanding of the dynamic interplay between multimedia communication and its ability to drive positive societal transformations.